Ceramic core with polymer corona hybrid nanocarrier for the treatment of osteosarcoma with co-delivery of protein and anti-cancer drug. (4th December 2017) - Prasad, S Ram; Kumar, T S Sampath; Jayakrishnan, A
Abstract: For the treatment of metastatic bone cancer, local delivery of therapeutic agents is preferred compared to systemic administration. Delivery of an anti-cancer drug and a protein that helps in bone regeneration simultaneously is a challenging approach. In this study, a nanoparticulate carrier which delivers a protein and an anti-cancer drug is reported. Bovine serum albumin (BSA) as a model protein was loaded into hydroxyapatite (HA) nanoparticles (NPs) and methotrexate (MTX) conjugated to poly(vinyl alcohol) was coated onto BSA-loaded HA NPs. Coating efficiency was in the range of 10–17 wt%. In vitro drug release showed that there was a steady increase in the release of both BSA and MTX with 76% of BSA and 88% of MTX being released in 13 days. Cytotoxicity studies of the NPs performed using human osteosarcoma (OMG-63) cell line showed the NPs were highly biocompatible and exhibited anti-proliferative activity in a concentration-dependent manner.